The economy of prostitution in the Roman world : a study of social history & the brothel - McGinn, Thomas A. J. (University of Michigan Press, 2004)
"This book is a study of the evidence for the business of female prostitution in the Roman world during the central part of Rome's history, a period extending from approximately 200 B.C. to A.D. 250. The main focus is on the economics of venal sex, meaning precisely the manner in which it was sold, a subject that extends to the ownership, operation, staffing, and location of brothels, as well as to various aspects of nonbrothel prostitution. Though the state of the evidence discourages any and all attempts at quantification, an attempt is made by the author to recover a sense of the role, the presence, and as much as is possible, the lived experience of prostitution city. Unlike most modern societies, the Roman political and legal authorities allowed the business of venal sex to proceed virtually unregulated, with a degree of tolerance that seems strange to a modern sensibility, but with consequences that emerge as sometimes equally foreign to us." "This book should appeal not only to a wide range of classicists, such as legal and social historians, archaeologists, and those interested in the status and role of women in antiquity, but also to scholars with similar specialties in other cultures and historical periods."--Jacket